Starting postgraduate medical training in general practice with a rotation in general practice – a qualitative study on experiences and effects - Becker, Christine; Stengel, Sandra; Roos, Marco; Altiner, Attila; Schwill, Simon (GMS Journal for Medical Education, 2024)
Objective: In Germany, the rotation into the general practitioner’s practice (GPP) as part of postgraduate medical training in general practice traditionally takes place at the end of the training period. The aim of this study was to explore possible subsequent effects of beginning training in the GPP from the perspective of general practitioners (GPs) and GP trainees. Methods: Nationwide, GPs and GP trainees were recruited who started specialization in GP in the GPP. Semi-structured telephone interviews were conducted between June and October 2022 using a self-developed interview-guide. The results were transcribed verbatim and analyzed using content analysis.Results: N=15 interviews were conducted, averaging 54 minutes (32-75 minutes) each (9 federal states, 4 GPs, 11 GP trainees). From the participants’ perspective, advantages included close supervision, flat hierarchies, more time for preparation and follow-up, self-directed learning as well as higher basic salary and regular working hours. Positive effects mentioned were reinforcement in career choice, early understanding of workflow in GPP, early development of a GP attitude and strengthening of professional self-confidence. Disadvantages included initial uncertainty at the beginning of the profession and limited opportunities for peer exchange. In conclusion, all participants would recommend beginning specialization with a rotation in the GPP.Discussion: Starting in GGP allows GP trainees to learn about GP in a self-directed, research-oriented manner and based on consultations which enables early professional identity formation. GP trainees should avoid lack of collegial support by participating in a postgraduate training program. In a second step, GP trainers perspectives need to be assessed.Conclusion: Beginning GP postgraduate training with a rotation in GP is advantageous and should be structurally promoted.